Analysis of the Relationship between Inflation and Interest Rates on Investment Decisions in the Capital Market: A Literature Review - Al Insani Mutiara Ramadhan; Wahyu Febri Ramadhan Sudirman (Global Sustainability Research Institute, 2026)
This study aims to analyze the relationship between inflation, interest rates, and investment decisions in the capital market based on a literature review. Inflation and interest rates are macroeconomic indicators frequently considered by investors when making investment decisions because they are related to investment returns and risk. This study employed a literature review method, reviewing various relevant scientific journal articles, books, and official publications. The literature was selected based on its relevance to the research topic, the credibility of the sources, and the recency of the publications to gain a comprehensive understanding of the relationships between the variables studied. The results of the literature review indicate that high inflation rates tend to reduce investor interest in the capital market due to reduced purchasing power and increased economic uncertainty. Furthermore, rising interest rates encourage investors to shift funds to financial instruments offering more stable returns, such as deposits and bonds. Conversely, controlled inflation and stable interest rate policies can create a conducive economic climate for investment growth in the capital market. Based on the synthesis of various literature, inflation stability and appropriate interest rate policies are important factors supporting capital market development and are key considerations in investment decision-making.